The legend of Zelda : Hyrule historia - Gombos, Michael; Himekawa, Akira (Milwaukie, OR : Dark Horse Books, 2013)
Gives historical information on The Legend of Zelda franchise, including the history of Hyrule and the official chronology of the games.
On the 25th anniversary of The Legend of Zelda / Shigeru Miyamoto -- The legend begins: the world of Skyward sword -- The history of Hyrule: a chronology -- Creative footprints: documenting 25 years of artwork -- Wrapping things up / Eiji Aonuma -- Special comic: The Legend of Zelda: Skyward sword / Akira Himekawa.
Originally published: [Tokyo] : Shogakukan Company, Limited, 2011.
Includes bonus manga comic: The legend of Zelda : skyward sword / by Akira Himekawa.
"All concept illustrations that originally contained handwritten notes in Japanese have been translated into English and updated for this version of the book."
Keywords: Legend of Zelda (Game) -- Miscellanea